Using BAM and CEP for Process Monitoring in Cloud BPM - Martínez Garro, José Nicolás (2016)
BAM (Business Activity Monitoring) and CEP (Complex Event Processing) have been deeply studied in traditional BPM, according to the procurement of relevant results about process execution, especially for improvement and monitoring purposes. Once BPM was introduced in the cloud and it was necessary to decompose processes in order to execute them in hybrid environments, the conception of monitoring has suffered several changes. In previous works we have designed an architecture for process execution and monitoring which considers several services in order to gather and show the recollected information as relevant results. A new approach over this architecture takes place in this work: it considers BAM and CEP as mechanisms for the information gathering process, and also enhances the monitoring application taking advantage of these two methodologies, now under the distributed perspective. Additionally we make a comparison about when it is convenient to use BAM or CEP alternatively in a distributed environment, according to the nature of the recollected data, the type of indicators needed to be shown and also the latency window over the data used as a source.